Teaching(s) From Dis-ease: Grieving, Teaching and Surrender - Elke, Ramona (Journal of the Canadian Association for Curriculum Studies, 2024)
This work is a conversation with my fears and wonder in the early days of the COVID pandemic, in which I had to live and work as a high school teacher, parent, scholar and artist. Through the weaving of my poems, paintings and life writing in an Indigenous Métissage, I reached for the teachings I have learned from my Elders and Ancestors, longing to find ways to stay human during those most inhumane days, when dis-ease was worsened by social injustice. Through the refracted world of the pandemic came the distressing news of recoveries of unmarked graves at the sites of former residential schools for Indigenous children. This news re-wrote me, unwound me, and re-routed the direction I longed to go to make learning spaces better for youth. Through poetic inquiry, I attempted to process these findings and asked Creator and All My Relations, how to be useful to the work of healing in this dis-ease.